De betrokkenheid van de communistische afgevaardigde Théo Dejace bij de partijcel Bensberg (1951-1961) - Bettens, Ludo; Geerkens, Eric (Studies over de sociaaleconomische geschiedenis van Limburg, 2018)
The commitment of the MP Théo Dejace to the Communist Party cell Bensberg, 1951-1961 This contribution uses a political fiction written by Théo Dejace, a Belgian communist MP, as a starting point. Through this story, Dejace outlines why he thinks it is essential to be involved in his neighbourhood and tells about the revival of a cell (the lowest structure in the Belgian Communist Party), called ‘cellule Bensberg’ (Liège). The first part reveals how fiction and biography are closely related, then gives some personal explanations of Dejace’s decision to take in charge the local cell. This commitment has also to be seen in the context of the political decrease of the Belgian communism after WWII. The core of the text describes first the socioeconomic environment of the Bensberg cell. It then focusses on the membership recruitment and the various activities to support the Party but also to retain members. This allows the reader to approach the local communist culture from below.